2019
DOI: 10.1039/c9mh00220k
|View full text |Cite
|
Sign up to set email alerts
|

Invoking ultralong room temperature phosphorescence of purely organic compounds through H-aggregation engineering

Abstract: Splitting energy (Δε)-controlled thermally activated reversed phase transformation from the low-lying dark state to the high-lying transition-allowed state of H-aggregation plays a key role in the organic ultralong room-temperature phosphorescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
97
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(98 citation statements)
references
References 42 publications
1
97
0
Order By: Relevance
“…The distinct dual‐emissive Cu I ‐NHC complexes differ from traditional Cu I complexes. The two separate emission bands with vibronic features are quite similar with the fluorescence and RTP from solid carbazole or Cz derivatives, suggesting singlet and triplet carbazole‐based transitions in these two Cu I complexes . In addition, the two Cu I complexes are analogous to a Au I complex [Au(Me 2 ‐imy)(cbz)] (Me 2 ‐imy=1,3‐dimethylimidazol‐2‐ylidene, cbz=carbazolate) in literature, which exhibits emission in a high‐energy band (404 nm) and low‐energy band (584 nm) in the crystalline solid.…”
Section: Resultsmentioning
confidence: 68%
“…The distinct dual‐emissive Cu I ‐NHC complexes differ from traditional Cu I complexes. The two separate emission bands with vibronic features are quite similar with the fluorescence and RTP from solid carbazole or Cz derivatives, suggesting singlet and triplet carbazole‐based transitions in these two Cu I complexes . In addition, the two Cu I complexes are analogous to a Au I complex [Au(Me 2 ‐imy)(cbz)] (Me 2 ‐imy=1,3‐dimethylimidazol‐2‐ylidene, cbz=carbazolate) in literature, which exhibits emission in a high‐energy band (404 nm) and low‐energy band (584 nm) in the crystalline solid.…”
Section: Resultsmentioning
confidence: 68%
“…Therefore, the significantly improved CP‐OURTP performance should be ascribed to the photo‐enhanced aggregation coupling including H‐aggregation and intra/intermolecular interactions of the chiral molecules in solid state . H‐aggregation has been proved to be effective to stabilize the highly active triplet excitons by suppressing both the radiative and non‐radiative rates for OURTP (Figure c) . Indeed, significant numbers of H‐aggregation were observed in the pristine single‐crystal (Figure S21) with positive exciton splitting energies (Δ ϵ ) ranging from 2.65×10 −5 to 2.81×10 −3 eV (Figure d and Table S9).…”
Section: Resultsmentioning
confidence: 99%
“…[31] H-aggregation has been proved to be effective to stabilize the highly active triplet excitons by suppressing both the radiative and non-radiative rates for OURTP Figure 3c). [32] Indeed, significant numbers of H-aggregation were observed in the pristine single-crystal ( Figure S21) with positive exciton splitting energies (De)r anging from 2.65 10 À5 to 2.81 10 À3 eV (Figure 3d and Table S9). From photoactivated single crystals,s tronger H-aggregation with enlarged De value resulted after photo-activation ( Figure S22).…”
Section: Angewandte Chemiementioning
confidence: 98%
“…Accordingly, the phosphorescence of C-dots was detected when they were incorporated into solids, such as polymer films [324]. In H-aggregated molecular assemblies of organic dyes, a bright room-temperature phosphorescence was achieved in solid powders [325] and even in water solutions [326] due to the fact of their special design [327]. Meanwhile, the basic mechanism of their triplet exciton generation [321,328] remains unclear as well as in nanocarbon systems.…”
Section: Triplet State Generationmentioning
confidence: 99%
“…Their generation is favored in H-aggregates formed by the charge-transfer dyes [39]. It was observed that the duration of phosphorescence in H-aggregates may be much longer than that of constituting molecules, by several orders of magnitude, reaching the level of second [327,329].…”
Section: Triplet State Generationmentioning
confidence: 99%